Grain & Noise - Artists in Synthetic Biology Labs Constructive Disturbances of Art in Science - Schmidt, Markus (Image, 2023)
The collaboration between scientists and artists in the form of Artist-in-Lab residencies may not only cause a productive disturbance for a day's work in the laboratory, but also reveal new ways of understanding. Research and science communication company Biofaction has brought together artists and synthetic biologists throughout Europe in a residence program that spans four truly cross-disciplinary collaborations. The contributors to this volume share their reflections of the dynamic frictions that occurred when their artistic and scientific worlds met. These stories, where chemistry labs, tobacco plants, genetically edited bacteria, and new-to-nature enzymes collide with music, photography, film, and visual arts, infuse the ongoing dialogue between art and sciences with grain, noise, and synergies.